The anti-biofilm compound 4-ethoxybenzoic acid inhibits Staphylococcus aureus virulence factor production via a putative 4EB-binding pocket in key virulence-associated proteins - Taylor, Caroline C.; Aviles-Gonzalez, Adonis; Marchesani, Alexander; Kiessling, Christina; Patrick, Travis; Chen, Linxin; Yao, Haozhe; Li, Zixuan; Seward, Abbie; Chin, Kuk-Jeong; Gilbert, Eric S. (Frontiers in Microbiology, 2026)
There is a need for dual action anti-virulence and anti-biofilm agents that target the opportunistic pathogen Staphylococcus aureus. Previous research determined that 0.8 mg/mL 4-ethoxybenzoic acid (4EB) reduced S. aureus ATCC 6538 biofilm formation by 88% relative to untreated controls with moderate inhibition of planktonic cell growth. Here we report that 4EB impacted S. aureus virulence phenotypes across all growth phases, including alpha-hemolysin (Hla) and serine protease (SplB/C) exoprotein production (60% reduction), staphyloxanthin pigment accumulation (73% reduction) and alpha-hemolysis (>87% reduction) compared to untreated control cells. RT-qPCR analysis demonstrated that 4EB downregulated virulence gene expression, including >100-fold reduction of alpha-hemolysin (hla) and leukocidins (lukDvEv), and a 35-fold decrease of the response regulator SaeR. Phenol-soluble modulin (PSM) transcription by biofilm-grown cells was upregulated by 4EB more than 4-fold for α1-4psm and β1-2psm genes, while δ-toxin (hld) was unaffected. In silico molecular docking analysis revealed that 4EB has a strong binding affinity (ΔG < −6.0 kcal/mol) for 9 virulence-associated transcriptional regulators, including SaeS, IcaR and CodY. Analysis of gene transcription during late exponential phase growth determined that genes controlled by 7 of the 9 identified regulators were significantly impacted by 4EB. The docking analysis identified putative 4EB binding sites that share common features including valine and tyrosine amino acid residues. The combined in vitro and in silico analyses identified interactions with well-known virulence genes but also implicated an effect of 4EB on proteins less commonly associated with S. aureus pathogenesis. These findings suggested potential alternative targets for anti-virulence and anti-biofilm therapeutics.